Design an Inventory Information System on General Administration Section of Polytechnic Harapan Bersama - Arif Rakhman; Muhamad Bakhar; Achmad Sutanto (West Science Information System and Technology, 2024)
The inventory information system used The general administration department still uses a manual system. Current systems use Microsoft Office Excel which causes the process of searching inventory data to be slow. Therefore, this research aims to make the system more efficient, easy to use, and can speed up information access and facilitate data or file management. The inventory system is very effective and efficient to use in general section units, especially logistics sub-divisions because the management of goods starting from procurement, inventory and transactions is recorded accurately. It is hoped that with this system, the process of processing university logistics goods data can run smoothly, quickly, with minimal errors, and information needs about university logistics can be obtained easily if at any time needed. The inventory system is very effective and efficient to use in general section units, especially logistics sub-divisions because the management of goods starting from procurement, inventory and transactions is recorded accurately.